Internalization of Learning Discipline for Low Grade Students in Elementary School: Internalisasi Kedisiplinan Belajar Siswa Kelas Rendah di Sekolah Dasar - Maisaroh, Indira; Supriyadi, Supriyadi (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to describe student learning discipline and teacher efforts in internalizing student learning discipline. The object of the research was conducted at the Kletek State Elementary School in Sidoarjo. The research subjects were 3 students and 1 class teacher. Data was collected using observation, interview and documentation techniques which were then analyzed using the Miles interactive analysis model, namely data collection, condensation, data presentation, drawing conclusions or data verification. The results showed that student learning discipline, including (1) attendance during school; (2) student obligations; (3) prohibition of students, and (4) wearing uniforms at school. Efforts to internalize learning discipline are carried out through the teacher being a role model for students, giving advice, being consistent in applying the rules, giving punishment to students who violate.